Thermally reduced graphenes exhibiting a close relationship to amorphous carbon - Wong, Colin Hong An (2013)
Graphene is an important material for sensing and energy storage applications. Since the vast majority of sensing and energy storage chemical and electrochemical systems require bulk quantities of graphene, thermally reduced graphene oxide (TRGO) is commonly employed instead of pristine graphene. The sp2 planar structure of TRGO is heavily damaged, consisting of a very short sp2 crystallite size of nanometre length and with areas of sp3 hybridized carbon. Such a structure of TRGO is reminiscent of the key characteristic of the structure of amorphous carbon, which is defined as a material without long-range crystalline order consisting of both sp2 and sp3 hybridized carbons. Herein, we describe the characterization of TRGO, its parent graphite material and carbon black (a form of amorphous carbon) via transmission electron microscopy, Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and cyclic voltammetry experiments. We used the data obtained as well as consideration of practical factors to perform a comparative assessment of the relative electrochemical performances of TRGO against amorphous carbon. We found out that TRGO and amorphous carbon exhibit almost identical characteristics in terms of density of defects in the sp2 lattice and a similar crystallite size as determined by Raman spectroscopy. These two materials also exhibit similar amounts of oxygen containing groups as determined by XPS and nearly indistinguishable cyclic voltammetric response providing almost identical heterogeneous electron transfer constants. This leads us to conclude that for some sensing and energy storage electrochemical applications, the use of amorphous carbon might be a much more economical solution than the one requiring digestion of highly crystalline graphite with strong oxidants to graphite oxide and then thermally exfoliating it to thermally reduced graphene oxide.